Implementasi Kurikulum Pendidikan Berbasis Islam pada Taman Kanak-Kanak Islam Terpadu - Nelda Arkas (Jurnal PAUD: Kajian Teori dan Praktik Pendidikan Anak Usia Dini, 2022)
The purpose behind this research is to investigate how the implementation of an Islamic-based education curriculum at the Integrated Islamic Kindergarten in Limau Sweet is related to its objectives, implementation methodology, and assessment strategy. For data collection techniques in the study, it was carried out by reviewing the results of observations, interviews and documentation with the object of exploration in research. The investigation was completed by an information triangulation strategy. The results obtained from the research are, planning an Islamic-based education curriculum means growing faith and commitment to Allah SWT, developing and expanding the attention of young people to practice Islamic religious lessons. The material for Islamic-based education programs is related to aqidah, worship, morals, muamalah, Al-Quran and prayer. In the implementation of learning the instructor uses various strategies, especially for improving the quality of Islam which is carried out through adjustment exercises that are carried out consistently. In addition, there is material on Integrated Islam in the underlying exercises in an Integrated manner. The madrasa assessment method uses performance, assignments, and observations (assessment of extraordinary al-Islam practice).Keywords: curriculum; education; Integrated Islamic Kindergarten.